The mineral evolution during coal washing and its effect on ash fusion characteristics of Shanxi high ash coals. (15th January 2018) - Kong, Lingxue; Bai, Jin; Li, Huaizhu; Chen, Xiaodong; Wang, Ji; Bai, Zongqing; Guo, Zhenxing; Li, Wen
Highlights: Quartz, kaolinite, and calcite removed from coal leads to the decreasing of S/A. The ash fusion characteristics were obviously influenced by the content of coal washing. A proper coal washing must be considered in gasification. Abstract: Gasification has been deemed as the most promising method for the thermochemical conversion of Shanxi high ash coals, although the use of these high ash coals leads to high consumption of coal and oxygen, low syngas yield and cold gas efficiency. In order to improve gasification efficiency, it is necessary to reduce the ash content of these Shanxi high ash coals. In this work, three representative Shanxi high ash coals were floated with ZnCl2 flotation agent to obtain floated coal samples with different ash contents. The mineral evolution during coal washing and its effect on ash fusion characteristics were thoroughly investigated. A radio frequency oxygen plasma furnace, X-ray diffraction (XRD) and SIROQUANT were used to analyze the variation of mineral compositions of the floated coals. Quartz (SiO2 ), kaolinite (Al2 (Si2 O5 )(OH)4 ), calcite (CaCO3 ), and tobelite (NH4 Al3 Si3 O10 (OH)2 ) were main mineral which were found in Shanxi high ash coals, and the high contents of quartz and kaolinite led to high AFTs (ash fusion temperatures) of these coals. As mineral content decreased, the contents of quarts, kaolinite, and calcite in the floated coals were obviously lowered, and this resulted in the decrease of S/A (mass ratio of SiO2 /Al2 O3 ) of the coal ashes. The ash fusion temperatures of Shanxi high ash coals were therefore significantly influenced by the extent of coal washing. Furthermore, the content of amorphous material in coals increased obviously with the decrease of ash content. These results have important implication in the selection of the appropriate coal washing procedure prior to gasification of these coals.